Sludge symphony: an analysis of the microbial diversity dynamics at play in the activated sludge process and the impacts thereof on wastewater treatment performance - Gouws, Francois (Stellenbosch : Stellenbosch University, 2025)
Gouws, Francois. 2024. Sludge symphony: an analysis of the microbial diversity dynamics at play in the activated sludge process and the impacts thereof on wastewater treatment performance. Unpublished masters dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131786